SNAI1-dependent upregulation of CD73 increases extracellular adenosine release to mediate immune suppression in TNBC - Hasmim, Meriem; Xiao, Malina; Van Moer, Kris; Kumar, Akinchan; Oniga, Alexandra; Mittelbronn, Michel; Duhem, Caroline; Chammout, Anwar; Berchem, Guy; Thiery, Jean Paul; Volpert, Marianna; Hollier, Brett; et al. (Frontiers in Immunology, 2022)
Triple-negative subtype of breast cancer (TNBC) is hallmarked by frequent disease relapse and shows highest mortality rate. Although PD-1/PD-L1 immune checkpoint blockades have recently shown promising clinical benefits, the overall response rate remains largely insufficient. Hence, alternative therapeutic approaches are warranted. Given the immunosuppressive properties of CD73-mediated adenosine release, CD73 blocking approaches are emerging as attractive strategies in cancer immunotherapy. Understanding the precise mechanism regulating the expression of CD73 is required to develop effective anti-CD73-based therapy. Our previous observations demonstrate that the transcription factors driving epithelial-to-mesenchymal transition (EMT-TF) can regulate the expression of several inhibitory immune checkpoints. Here we analyzed the role of the EMT-TF SNAI1 in the regulation of CD73 in TNBC cells. We found that doxycycline-driven SNAI1 expression in the epithelial TNBC cell line MDA-MB-468 results in CD73 upregulation by direct binding to the CD73 proximal promoter. SNAI1-dependent upregulation of CD73 leads to increased production and release of extracellular adenosine by TNBC cells and contributes to the enhancement of TNBC immunosuppressive properties. Our data are validated in TNBC samples by showing a positive correlation between the mRNA expression of CD73 and SNAI1. Overall, our results reveal a new CD73 regulation mechanism in TNBC that participates in TNBC-mediated immunosuppression and paves the way for developing new treatment opportunities for CD73-positive TNBC.